Late-Onset Alcohol Abuse as a Presenting Symptom of Neurodegenerative Diseases. - de Paula França Resende, Elisa; Ketelle, Robin; Karydas, Anna; Allen, Isabel; Grinberg, Lea T; Spina, Salvatore; Seeley, William W; Perry, David C; Miller, Bruce; Naasan, Georges (J Alzheimers Dis, 2022)
BACKGROUND: The association between lifetime alcohol abuse and a higher risk to develop dementia is well known. However, it is unknown whether older adults who begin abusing alcohol late in life have an underlying neurodegenerative disease. OBJECTIVE: Identify the frequency of lifelong alcohol abuse (L-AA), late-onset alcohol abuse (LO-AA), and alcohol abuse as a first symptom of dementia (AA-FS) in patients with neurodegenerative diseases. METHODS: Cross-sectional retrospective study of patients evaluated at an academic referral center with a clinical diagnosis of behavioral variant frontotemporal dementia (bvFTD), Alzheimer-type dementia (AD), and semantic variant primary progressive aphasia (svPPA) (n = 1,518). The presence of alcohol abuse was screened with the National Alzheimer's Coordinating Center questionnaire. L-AA was defined as onset <  40 years, LO-AA as onset ≥40 years, and AA-FS was defined when the abuse started within the first three years from symptom onset. RESULTS: The frequency of LO-AA was 2.2% (n = 33/1,518). LO-AA was significantly more frequent in patients with bvFTD than AD (7.5%, n = 13/173 versus 1.3%, n = 16/1,254, CI:1.0;11.4%), but not svPPA (4.4%, n = 4/91, CI: -4.4;10.7%). Similarly, AA-FS was more frequent in bvFTD patients than AD (5.7%, n = 10/173 versus 0.7%, n = 9/1,254, CI:0.5% ;9.5%), but not svPPA (2.2%, n = 2/91, CI:-2.4;9.1%). CONCLUSION: LO-AA can be a presenting symptom of dementia, especially bvFTD. Alcohol abuse onset later in life should prompt a clinical investigation into the possibility of an underlying neurodegenerative process because delay in diagnosis and treatment may increase patient and caregiver burden. The results need to be interpreted with caution due to the limitations of the study.

Predicting regional neurodegeneration from the healthy brain functional connectome. - Zhou, Juan; Gennatas, Efstathios D; Kramer, Joel H; Miller, Bruce L; Seeley, William W (Neuron, 2012)
Neurodegenerative diseases target large-scale neural networks. Four competing mechanistic hypotheses have been proposed to explain network-based disease patterning: nodal stress, transneuronal spread, trophic failure, and shared vulnerability. Here, we used task-free fMRI to derive the healthy intrinsic connectivity patterns seeded by brain regions vulnerable to any of five distinct neurodegenerative diseases. These data enabled us to investigate how intrinsic connectivity in health predicts region-by-region vulnerability to disease. For each illness, specific regions emerged as critical network "epicenters" whose normal connectivity profiles most resembled the disease-associated atrophy pattern. Graph theoretical analyses in healthy subjects revealed that regions with higher total connectional flow and, more consistently, shorter functional paths to the epicenters, showed greater disease-related vulnerability. These findings best fit a transneuronal spread model of network-based vulnerability. Molecular pathological approaches may help clarify what makes each epicenter vulnerable to its targeting disease and how toxic protein species travel between networked brain structures.
Keywords: Aged; Atrophy; Brain; Brain Mapping; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neural Pathways; Neurodegenerative Diseases; Oxygen; Reference Values